Monitoring of Organochlorine Pesticides Residues in Five Fruits using Gas Liquid Chromatography Equipped with Electron Capture Detector (GLC-ECD) - Kumar, Devendra; Sharma, Shiva (Asian Journal of Chemistry, 2019)
India is the largest producer of fruits as they are important part of their economy. But they are badly affected by insect-pest attack during harvesting. Farmers use a large amount of pesticides to protect them but due to their longer persistence they found in fruits in small quantities. This paper described an analytical methodology for the monitoring of 20 organochlorine pesticides in 5 fruits viz. pineapple (Ananas comosus), apple (Malus pumila), plum (Prunus domestica), papaya (Carica papaya) and mango (Mangifera indica) by using gas liquid chromatography equipped with electron capture detector (GLC-ECD). During the monitoring work it has been found that each fruit was contaminated with pesticides. Pineapple was found contaminated with β-BHC, δ-BHC, heptachlor epoxide, dieldrin, endrin and methoxychlor; apple was found contaminated g-BHC, δ-BHC, heptachlor epoxide, dieldrin, endrin, endosulfan II and methoxychlor; plum and papaya were found contaminated with g-BHC, β-BHC, δ-BHC, heptachlor epoxide, 4,4′-DDE, endrin, endosulfan sulfate and methoxychlor; mango was found contaminated with β-BHC, δ-BHC, 4,4′-DDE, endrin, endosulfan sulfate and methoxychlor. However, the detected concentration of pesticides was below the MRL values but their long term use can cause serious health problems.